Fiber-optic communication systems - Agrawal, G. P. (Govind P.), 1951- (New York : Wiley, 2010)
'This book provides a comprehensive account of fiber-optic communication systems. The 3rd edition of this book is used worldwide as a textbook in many universities. This 4th edition incorporates recent advances that have occurred, in particular two new chapters. One deals with the advanced modulation formats (such as DPSK, QPSK, and QAM) that are increasingly being used for improving spectral efficiency of WDM lightwave systems. The second chapter focuses on new techniques such as all-optical regeneration that are under development and likely to be used in future communication systems. All other chapters are updated, as well.'--
Book is accompanied by one Cd entitled' Fiber-optic communication systems, 4th ed.' bearing the same call number and available at Bahagian Koleksi Media
Keywords: Optical communications; Fiber optics